2018
DOI: 10.1126/scisignal.aan3677
|View full text |Cite
|
Sign up to set email alerts
|

“Disruptor” residues in the regulator of G protein signaling (RGS) R12 subfamily attenuate the inactivation of Gα subunits

Abstract: Understanding the molecular basis of interaction specificity between RGS (regulator of G protein signaling) proteins and heterotrimeric (αβγ) G proteins would enable the manipulation of RGS-G protein interactions, explore their functions, and effectively target them therapeutically. RGS proteins are classified into four subfamilies (R4, R7, RZ, and R12) and function as negative regulators of G protein signaling by inactivating Gα subunits. We found that the R12 subfamily members RGS10 and RGS14 had lower activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…4b). The electrostatic dominance in interactions of RGS domains with Gα subunits was also observed in interactions of Gα o and Gα i with various RGS domains 46 . The number of Gα q residues that contribute to interactions with RGS2 and RGS8 are 27 and 25, respectively.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…4b). The electrostatic dominance in interactions of RGS domains with Gα subunits was also observed in interactions of Gα o and Gα i with various RGS domains 46 . The number of Gα q residues that contribute to interactions with RGS2 and RGS8 are 27 and 25, respectively.…”
Section: Resultsmentioning
confidence: 73%
“…This region was shown to participate in the binding of Gα subunits to effectors, such as the binding of Gα s to adenylyl cyclase 43 . RGS proteins were shown to substantially interact with the Gα GTPase domain, yet were also shown to interact with the Gα helical domain 37,38,4446 . More recently, it was suggested that the helical domain is a major determinant of the specific interactions between Gα q and RGS2 47 .…”
Section: Introductionmentioning
confidence: 99%
“…We followed the methodology described previously to analyze the per‐residue contributions of Ang2 and Tie2 residues to intermolecular interactions in the complex (Supporting Information Figure S1). The finite difference Poisson‐Boltzmann (FDPB) method was used to calculate the net electrostatic and polar contributions (ΔΔG elec ) of each residue that is within 15 Å of the dimer interface.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the methodology described previously 32,[36][37][38][39][40] to analyze the per-residue contributions of Ang2 and Tie2 residues to intermolecular interactions in the complex (Supporting Information Figure S1).…”
Section: Energy Calculations To Identify Residues That Contribute Dmentioning
confidence: 99%
“…To map the individual residues that contribute to colicin/pyocin-immunity protein interactions, we analyzed the representative X-ray structures of colicins bound to their immunity proteins, using an energybased computational methodology developed previously by our lab [55][56][57][58][59][60][61] . As described in the "Materials and methods" sectio, we calculate the net electrostatic/polar contributions (ΔΔG elec ) of each residue ≤ 15 Å of the colicin-immunity protein interfaces.…”
Section: Residue-level Mapping Of the Interactions Of Colicins With Tmentioning
confidence: 99%